Self-Assessment for Building Creativity in Writing Essay about ‘Entrepreneurial Mindset’ - Mulyanto Mulyanto; Hadi Sugianto; Sudarwati Sudarwati; Putut Handoko (Ridwan Institute, 2022)
One of the biggest problems faced by developed countries in the world is concerned with the increase of unemployment from day to day. Lacks of building the entrepreneurial mindset among people in society may support the existing problem which can exacerbate the economic conditions in the developed countries nowadays. This study investigated the students’ entrepreneurial mindset seen from their opinions written down in their essay. A quantitative approach within a survey design was applied in the study. 50 students from English department of the Faculty of Letters, Universitas Negeri Malang (UM) and Universitas Dr. Soetomo Surabaya (Unitomo) were chosen to be the participants in the study. The study also used a questionnaire and a depth-interview as the instruments. The results showed that students’ creativities in writing essay about building the entrepreneurial mindset were low. It could be seen from the creativity aspects including curiosity, flexibility, and originality in finding and developing new ideas in their writings. And also, the students’ lacks of creativity were also influenced by their unwillingness to build and to do business due to some obstacles such as having no parents’ permissions, business skills and experiences, business relations, and having other plans of working referring to their background knowledge and titles gained. The study implies that entrepreneurial mindset actually can be the alternative topic to build the students’ creativities in writing essay which are beneficial not only for their writing skill improvement, but also for their thinking development in solving the problems about unemployment through being entrepreneurs in the future.